Tinjauan Kerentanan, Risiko dan Zonasi Rawan Bahaya Rockfall di Kulonprogo, Yogyakarta - Dyah R. Hizbaron; Danang Sri Hadmoko; Samodra Wibawa; Syarifah Aini Dalimunthe; Junun Sartohadi (Forum Geografi, 2010)
This research aims at identification of spatial plan zonation in rock fall prone areas. Research method applies hazard, vulnerability and risk analysis as an input for spatial modeling using Multi Criteria Evaluation (MCE). Research reveals that in Girimulyo is susceptible towards rock fall. In the last decades, there were 16 occurrences of rock fall that impacted to physical damages. Fortunately, such disaster did not cause any harm to human life. Therefore, research argue that physical vulnerability analysis can be analyzed, while social vulnerability cannot be analyzed further, since it had less data support. According to the research, there are more than 48 housing units located in hazard zone. Hence, local government should initiate structural mitigation to avoid further loss. Research also reveals that areas with high susceptibility will not directly consider as high risk zone, unless it has high vulnerability index. Example: areas along escarpment, where it has high susceptibility, but it has no element at risk in the area. Thereby, research tries to present zonation for prone hazard areas, using risk index. The result is quite representative, since possible areas to be developed is anywhere alongside road network. Indication of the area is produced from the multi criteria analysis. Multi criteria analysis is an essential method to combine spatial data and its attribute. Using such method requires more data input and expertise in justifying indicator to be selected.